Implementation of Customary Marriage of Nuaulu Tribe People as Civic Culture in Sepa Country, Amahai District - Sopalatu, Najwa; Sialana, Fatimah; Tuharea, Jumiati (CV. Rayyan Dwi Bharata, 2023)
Traditional marriages in the Nuaulu tribe community usually begin with a request or proposal made by the male family through a messenger or spokesperson who is commonly referred to as ruetawamana. This was done on the basis of the young man and the girl who had made an agreement to marry. So that what parents do is just to fulfill rituals and carry out the provisions of applicable customary law. The rituals in the traditional marriage process which are usually carried out at the time of marriage are usually accompanied by an exchange of property between the man and woman and then followed by a blessing ritual led by the chief of the tribe by praying specifically and to unite and bind as proof that they are truly married. it is true that husband and wife who are legal in the eyes of customary law are to cover both parties with the sarongs that have been prepared. The author of this thesis discusses